Xenoglossophilia in Asian skincare marketing: A cross-country multiple case analysis of language choice on social media - Fatmasari, Fajria; Setiadi, Rizki Muhammad Ardian (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
The occurrence of xenoglossophilia in non-English speaking countries has recently become attention among scholars due to the rise of technology. It makes it easier for brands to promote through social media content. Some skincare brands routinely post content to attract the market, thus making skincare marketing so dynamic. The objective of this paper is to explore the phenomenon of xenoglossophilia in certain countries and provide a new understanding of how English dominance, the absence of a native language, and script choice impact the situation. Thus, this study will contribute to marketers, linguists, and academics. This research was a multiple-case analysis that employed multiple-analyst triangulation in analyzing data on social media content from some brands in Indonesia, Japan, South Korea, Thailand, and China. The results of the study showed English was chosen for their promotional text. Surprisingly, brands from Indonesia have 0,005 percent of full native language frequency in their content, while brands from China employ 100 percent English in their content. Here, English was seen as the dominant language among the countries, although they still had their native language. The absence of the native language is seen in some brands from some countries for any reason. Therefore, some brands still consider having copywriting in their native script related to their main target audience. From the data, we concluded that the use of English in social media content is considered a strategy to gain more market share in the global economy without purposefully irritating nationalism among the countries.